Edukasi Pertanian Ramah Lingkungan di Desa Pungka, Kabupaten Sumbawa - Nurul Amri Komarudin; Yuni Yolanda; Syamsul Hidayat; Pramudya Bagas Utama; Chairul Anam Afgani; Beata Ratnawati; Rifqi Rahmat Hidayatullah; Leonard Dharmawan (Jurnal Abdimas Madani dan Lestari (JAMALI), 2022)
This service activity was carried out in Pungka Village, Unter Iwes District, Sumbawa Regency, West Nusa Tenggara in June-July 2022. The agricultural sector is the main source of livelihood for residents in Pungka Village, but there are still many residents in Pungka Village who have not applied environmentally friendly agricultural activities, where around 90% of farmers use chemical fertilizers in their agricultural activities, around 85% carry out biomass burning activities left over from the harvest such as straw left over from rice crops and fronds of corn and sugarcane harvest residues, in addition, there are about 90% of farmers who use pesticides with doses that are not in accordance with the procedure for use. So that all of that can lead to an increase in the contribution of greenhouse gas (GHG) effects such as CH4 from paddy fields, CO2 and N2O from biomass fertilization and burning activities. So it can be said that agricultural activities in Pungka Village are still not environmentally friendly, therefore it is necessary to carry out counseling or socialization activities related to how to farm a healthy and environmentally friendly farming system. The purpose of this service activity is to educate farmers in Pungka Village regarding environmentally friendly farming methods by socializing organic farming systems, so that it is expected to ensure the sustainability and sustainability of agriculture and the environment in Pungka Village. So that the agricultural products are expected to be healthy for those who consume and preserve the surrounding environment